АЙДАР-АРНАСОЙ КЎЛЛАР ТИЗИМИДА ТУРИЗМНИ РИВОЖЛАНТИРИШ ИМКОНИЯТЛАРИ - Усманов, М.Р.; Абдираманов, Ж.Б. (SCIENCE and SOCIETY, 2023)
This article is presented on the formation of the Aydaro-Arnasoy lake system, the organization of tourism in the Aydaro-Arnasoy lake system, ecotourism, and the development of tourism routes.
Keywords: Aydar-Arnasoy lake system; tourism; ornithologists of the world; ecotourism; "comfortable distance" zone; hunting tourism; Arab tourists; tourism routes; boat and flotilla hotels